Study of the functional properties and anti-oxidant activity of pea protein irradiated by electron beam. (June 2017) - Wang, Li; Zhang, Xinxia; Liu, Fengru; Ding, Yuanyuan; Wang, Ren; Luo, Xiaohu; Li, Yanan; Chen, Zhengxing
Abstract: The effects of electron bean irradiation (EBI) on pea protein hydrolysates were examined. The EBI treatment of pea proteins results in an increase in the emulsifying properties of their hydrolysates. A dose-dependent phenomenon was observed, with the maximum effect occurring at 50 kGy. Both foaming capacity and stability increase as the irradiation dose increases and reaches a maximum at 10 kGy. Additionally, hydrolysates pre-irradiated at 50 kGy have the strongest scavenging effect, with the DPPH radical and ABTS + radical scavenging activity levels increasing by 32.73% and 52.80%, respectively, compared to the control. Pretreatment with EBI prior to protease hydrolysis markedly increases surface hydrophobicity values of the hydrolysates when compared to the control. As the irradiation dose increases, the surface hydrophobicity values increase and eventually reach a maximum value of 174.09%. The molecular weight percentages for < 3 kDa fractions increases from 83.97% to 94.07% after 50 kGy electron beam irradiation treatment. Highlights: EBI can improve emulsifying and foaming properties of PPHs with suitable does. Antioxidant activity was enhanced by EBI as irradiation dose increased. Surface hydrophobicity (S0) increased and molecular weight (MW) reduced. S0 and MW play an important role in modification of functional ability of PPHs. There was positive relation between MW and antioxidant activity of EPPHs.